Assessment of suicidal risk in elderly - Rudytė, Rasa; Sargautytė, Rūta (Psichologija, 1998)
The suicide rate is increasing in Lithuania, therefore it is very important to estimate the reasons of suicides in the target age groups. The aim of this study was to appraise the social environment, chronic illness and some demographic characteristics as the suicidal risk factors in elderly. The suicidal risk was assessed by Purpose in Life Test, Beck Hopelessness Scale, Chronic Illness Problem Inventory and a Semi-structured interview. Sixty chronically ill subjects from 60 to 80 years old were assessed, 30 of them residing privately or with their families, and other 30 - in governmental institutions for the care of elderly. The suicidal risk in the elderly was estimated as high. Various chronic illnesses caused problems in daily and social activity, interrupted relationships with family members and friends. Elderly residing in boarding houses experienced significantly lower feeling of the purpose in life, higher hopelessness level and more severe psychosocial problems. Singleness, absence of children and/or grandchildren decreased the psychological well-being and enhanced suicidal risk in elderly, especially those residing in boarding houses.